Population structure and genetic diversity of the giant anteater (Myrmecophaga tridactyla: Myrmecophagidae, Pilosa) in Brazil - Clozato, Camila L.; Miranda, Flávia R.; Lara-Ruiz, Paula; Collevatti, Rosane G.; Santos, Fabrício R. (Genetics and molecular biology, 2017)
The giant anteater (Myrmecophaga tridactyla, Pilosa, Linnaeus 1758) belongs to the mammalian order Pilosa and presents a large distribution along South America, occupying a great variety of habitats. It is listed in the IUCN Red List of threatened species as Vulnerable. Despite threatened, there is a lack of studies regarding its genetic variability. The aim of this study was to examine the genetic diversity and patterns of genetic structure within remaining populations. We analyzed 77 individuals from seven different populations distributed in four biomes across Brazil: Cerrado, Pantanal, Atlantic Forest and Amazon Forest. We sequenced two mitochondrial markers (control region and Cyt-b) and two nuclear markers (AMELY and RAG2). We found high genetic diversity within subpopulations from National Parks of Serra da Canastra and Emas, both within the Cerrado biome, with signs of population expansion. Besides, we found a notable population structure between populations from the Cerrado/Pantanal and Amazon Forest biomes. This data is a major contribution to the knowledge of the evolutionary history of the species and to future management actions concerning its conservation.